1998
DOI: 10.1007/bf02739949
|View full text |Cite
|
Sign up to set email alerts
|

Columnar cell carcinoma of the thyroid: MIB-1 immunoreactivity as a prognostic factor

Abstract: We report a case of columnar cell carcinoma of the thyroid. A 47-year-old Japanese man had a nonencapsulated thyroid mass that infiltrated the surrounding tissues extensively. Seventeen months after thyroidectomy he died of respiratory failure resulting from tracheal invasion. An autopsy showed distant metastases to the liver, lung, esophagus, and pancreas. Histologically, the thyroid mass consisted of tall columnar atypical cells with marked nuclear stratification, About one-fifth of tumor cells were immunopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…The MIB-1 index in our series is much lower than that in the aggressive variant of PC reported by Katoh et al 32,33 Our pathological findings (lymphoid stroma, low proliferative activity, S100 protein-positive dendritic/Langerhans cells) are compatible with the previously reported data associated with favourable biological behaviour of PC. [30][31][32][33] On the other hand, the strong membrane positivity of Leu-M1 in the neoplastic cells of all our cases must be taken into consideration. Schröder et al reported a strong correlation between Leu-M1 positivity in thyroid PC and its advanced clinical stage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The MIB-1 index in our series is much lower than that in the aggressive variant of PC reported by Katoh et al 32,33 Our pathological findings (lymphoid stroma, low proliferative activity, S100 protein-positive dendritic/Langerhans cells) are compatible with the previously reported data associated with favourable biological behaviour of PC. [30][31][32][33] On the other hand, the strong membrane positivity of Leu-M1 in the neoplastic cells of all our cases must be taken into consideration. Schröder et al reported a strong correlation between Leu-M1 positivity in thyroid PC and its advanced clinical stage.…”
Section: Discussionsupporting
confidence: 90%
“…The average MIB‐1 index in our cases was approximately 3.5%, thus not differing significantly (analysis of variant test ( ANOVA ), P < 0.05) from the average MIB‐1 index in classical PC (3.9%) which we had found in a previous study of classical PC (unpublished data). The MIB‐1 index in our series is much lower than that in the aggressive variant of PC reported by Katoh et al 32 , 33 . Our pathological findings (lymphoid stroma, low proliferative activity, S100 protein‐positive dendritic/Langerhans cells) are compatible with the previously reported data associated with favourable biological behaviour of PC 30–33 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous reports have documented an elevated mitotic index of 2-13 per 10 HPF and a Ki-67 labeling index of approximately 20% in aggressively behaving columnar cell carcinomas. 3,6,34,36,47 In this study, the overall Ki-67 index in columnar cell carcinoma was greater than that previously reported in conventional papillary thyroid carcinomas. 59,68 However, Ki-67 labeling of neoplasms presenting at low and high tumor staging was widely variable and overlapping; indolent tumors exhibited Ki-67 proliferation indices of up to 30%, whereas an aggressive tumor displayed a Ki-67 index of less than 5%.…”
Section: Discussioncontrasting
confidence: 72%
“…Because previous studies of these neoplasms have been largely limited to case studies, we reviewed reports in the English literature to date to better define the clinicopathological characteristics of these rare neoplasms. [1][2][3][4][5][6][7][8][9][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The 48 reported cases consisted of 15 men and 33 women. Men ranged in age from 29 to 77 years (mean 49.5 years, median 47 years) and women from 16 to 83 years (mean 49 years, median 50 years).…”
Section: Discussionmentioning
confidence: 99%